2020
DOI: 10.1111/jgs.16907
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Performance of Frailty for Delirium and Functional Decline in Vascular Surgery Patients

Abstract: Background Frailty in older vascular surgery patients is associated with increased mortality, hospital stay, and morbidity. The association of frailty with hospital‐acquired geriatric syndromes such as delirium and functional decline has not been well studied. Objectives To investigate the association between frailty and hospital‐acquired geriatric syndromes in older hospitalized vascular surgery patients, and to evaluate the prognostic performance of the frailty index (FI) and the Clinical Frailty Scale (CFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…In summary, the study by Thillainadesan et al found that up to one‐third of older vascular surgery inpatients have frailty and that baseline frailty is associated with hospital‐acquired geriatric syndromes, most notably delirium 4 . This study highlights the critical need for surgical research to incorporate geriatric‐focused predictors and patient‐centered outcomes.…”
Section: Figurementioning
confidence: 74%
See 4 more Smart Citations
“…In summary, the study by Thillainadesan et al found that up to one‐third of older vascular surgery inpatients have frailty and that baseline frailty is associated with hospital‐acquired geriatric syndromes, most notably delirium 4 . This study highlights the critical need for surgical research to incorporate geriatric‐focused predictors and patient‐centered outcomes.…”
Section: Figurementioning
confidence: 74%
“…Data are lacking on how surgical interventions impact outcomes valued by older adults and on how baseline geriatric conditions such as frailty may influence these outcomes following surgery. The study by Thillainadesan et al in this issue addresses this knowledge gap for the burgeoning population of older adults undergoing vascular surgery 4 . The authors had two objectives: (1) to evaluate the associations between frailty and multiple hospital‐acquired geriatric syndromes and (2) to measure the utility of two validated frailty indices in predicting the hospital‐acquired geriatric syndromes of delirium and functional decline.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations